Pengaruh Kepemimpinan, Keseimbangan kehidupan kerja dan Pengembangan Karir terhadap Kinerja Organisasi - Ida Oetari Poernamasari; Adi Muhajirin; Hapzi Ali (Dinasti Publisher, 2023)
The Effect of Kepemimpinan, Keseimbangan kehidupan kerja and Pengembangan Karir on Organizational Performance is a scientific article of literature study in the scope of human resources. Objectives This study aims to evaluate the influence of three main factors, namely Kepemimpinan, keseimbangan kehidupan kerja, and task complexity on organizational performance. Kepemimpinan is identified as the first independent variable, focusing on Kepemimpinan style and the leader's ability to motivate and guide the team. The second independent variable is work-life balance, which reflects the extent to which employees can integrate their personal and professional lives. Meanwhile, task complexity is considered as the third independent variable, evaluating the level of difficulty and complexity of tasks faced by organizational members. This research uses a literature review approach to identify the relationship and influence between the variables under study. The research results are expected to provide a better understanding of how these factors interact with each other and contribute to organizational performance. The object of research on online libraries, Google Scholar, Mendeley and other academic online media. Research method with library research sourced from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) Kepemimpinan affects organizational performance; 2) Keseimbangan kehidupan kerja affects organizational performance; and 3) Task complexity affects organizational performance.